Som + imagem - Puccini, Sérgio (Imagofagia, 2021)
Sobre SÁ, Simone Pereira de & COSTA, Fernando Morais da (orgs.). Som + imagem. Rio de Janeiro: Editora 7 Letras, 2012. 235pp. ISBN: 978-85-7577-946-0. Palabras clave: reseña, Simone Pereira de SÁ, Fernando Morais da Costa, Som + imagem